Problems with the Organization of Forensic Medicine and Non-Forensic Fields in Forensic Sciences in Turkey: Assessment with Two Reports - Doğan, Muzaffer Berna (The Bulletin of Legal Medicine, 2022)
Forensic science is a superstructure that includes many branches that require special expertise. The correct application of these branches that require expertise to the practice requires a unique organization. The way to establish an organization in this way is strictly dependent on evaluating the problems from both inside and outside. For the holistic approach to the problems related to forensic science and forensic medicine organization in Turkey, current literature on the subject was studied and two resources have been reached. The first of these is a study prepared by the Presidency State Supervisory Board (DDK) in 2010. The main perspective in this study is to provide European Union norms. The other study is a report titled "Forensic Medicine Service Model and Manpower Planning" prepared by Prof. Dr. Yasemin Balcı, after being discussed by the Board of Proficiency in Forensic Medicine and accepted on 7 April 2007. Although many researches have been carried out on the field until today, these two reports come to the fore in which many areas and issues are discussed extensively and recommendations are made. It is seen that the problems stated in these detailed reports evaluated within this scope, there are deficiencies in the implementation of the structures and regulations proposed to solve the problems. For this reason, first of all, any regulation and structuring that has been made to solve the problems stated in these reports has been discussed when necessary.
Keywords: Forensic science, forensic medicine, medico-legal practices